«One prick and then it´s done»: a mixed-methods exploratory study on intramuscular injection in heroin-assisted treatment - Maximilian Meyer; Ramón Eichenberger; Johannes Strasser; Kenneth M. Dürsteler; Marc Vogel (BMC, 2021)
Abstract Background Intramuscular (IM) injection of drugs is associated with high rates of injecting-related injuries and diseases. However, little is known about the role of this route of administration in heroin-assisted treatment. The aim of this study was to determine the prevalence of IM diacetylmorphine administration and associated complications as well as to explore patients' views and opinions on the topic and the underlying reasons for this practice. Methods The research site was a Swiss outpatient treatment centre specialised in heroin-assisted treatment. We conducted in-depth interviews with two patients who intramuscularly inject diacetylmorphine. Interviews were analysed qualitatively, and emerging themes were used to develop a 38-item questionnaire on IM injections. We then offered this questionnaire to all patients in the treatment centre. Results Five main themes emerged from the in-depth interviews: poor venous access, side effects, subjective effects, procedure for IM injection, and consideration of alternatives to IM. These themes covered the rationale for using this route of administration, complications, subjective effects of IM diacetylmorphine, hygiene and safety measures as well as alternative routes of administration. Fifty-three patients filled in the questionnaire. The lifetime prevalence of IM injections was 60.4% (n = 32) and 34.4% (n = 11) of the patients stated that IM injection was their primary route of administration. No participant reported using the IM route for street drugs. The main reason for IM injections was poor vein access. Other reasons given were time saving and less risk of injuries. Complications included induration of muscle tissue and pain, whereas more severe complications like thrombosis and infections of the injection site were reported much less often. Conclusion As the population of opioid-dependent individuals is aging and the deterioration of access veins is likely to increase, the frequency of IM injecting will equally increase. Even though our data show that the IM injection of diacetylmorphine in a clinical setting is a common practice and appears to be relatively safe, research on alternative routes of administration is needed to provide potentially less harmful alternative routes of administration in heroin-assisted treatment.